ALIH FUNGSI LAHAN SEBAGAI ANCAMAN KELESTARIAN HUTAN DULAMAYO UTARA, KECAMATAN TELAGA BIRU, KABUPATEN GORONTALO, PROVINSI GORONTALO - Miftahul F. Adudu; Triyana Sefya Saleh; Sitti Rahmatia Mooduto; Dewi Wahyuni K. Baderan (UIN Sunan Gunung Djati Bandung, 2023)
North Dulamayo Forest is one of the forests that are rich in both biological and non-biological natural resources. This natural wealth is used as a source of life for the local community to meet their daily needs. As a result of the conversion of forest functions into agricultural land, the surrounding community, animals, plants, and the environment as a whole. This study aims to obtain information on the physical condition and impact of land conversion in the North Dulamayo Forest area, Telaga Biru District, Gorontalo Regency, and Gorontalo Province. The research method used is descriptive qualitative. The subjects in this study were people living around the forest. Collecting data using observation, interview, and documentation techniques. The results of the study found that the people around the Dulamayo Forest chose to convert the forest into agricultural land to meet their daily needs. The transfer of function has an impact on forest destruction, reducing the number of flora and habitats of various animals in the North Dulamayo Forest. Another impact that often occurs is the cause of landslides in the rainy season.